Einfluß von großflächigen Reliefumgestaltungen bei Flurbereinigungen in südbadischen Weinbaugebieten auf Landschafts- und Wasserhaushalt - Morgenschweis, Gerd; Luft, Gerhard (ERDKUNDE, 1985)
The problems of large-scale, terraced land consolidation together with water management improvements carried out on loessial areas in the viticulture region of southern Baden (Southern Germany) are demonstrated, taking as an example two schemes on the eastern Kaiserstuhl hills. The consequences of these large-scale changes of relief on topoclimate (movement of cold air, upcurrents), soil water balance (augmented soil moisture in the main root zone and consequences for vegetative growth), erosion (slumping) and run-off characteristics are shown. The influences on hydrological processes are quantified by comparing two small adjoining experimental basins (a long-standing small-terraced basin, a large-terraced basin) on the Eichstetten landmark. First results indicate a significant increase of peak discharge and the danger of flooding in the consolidation basins. The problems of the acquisition and evaluation of hydrological data, as well as the results of detailed model calculations on run-off formation, are shown. Beside being of scientific interest, the results are of use in the planning of new land consolidation projects together with water management improvements.